2013
DOI: 10.1038/ncomms2582
|View full text |Cite|
|
Sign up to set email alerts
|

MacroH2A histone variants act as a barrier upon reprogramming towards pluripotency

Abstract: The chromatin template imposes an epigenetic barrier during the process of somatic cell reprogramming. Here, using fibroblasts derived from macroH2A double knockout mice we show that these histone variants act cooperatively as a barrier to induced pluripotency. Through manipulation of macroH2A isoforms, we further demonstrate that macroH2A2 is the predominant barrier to reprogramming. Genomic analyses reveal that macroH2A1 and macroH2A2, together with H3K27me3, co-occupy pluripotency genes in wild type fibrobl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
198
2
9

Year Published

2014
2014
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 178 publications
(234 citation statements)
references
References 58 publications
(95 reference statements)
17
198
2
9
Order By: Relevance
“…We did not see evidence that macroH2As have a crucial role in differentiation or morphogenesis during embryonic development, in contrast to some studies of in vitro ES cell differentiation and early zebrafish development (20)(21)(22). Interestingly, other studies of ES cells (42) or induced pluripotent stem cells (43) found that macroH2As are not required for in vitro differentiation and thus appear to be compatible with our results with macroH2A KO mice. While the increased perinatal death that we see in C57BL/6 double KOs could involve developmental defects that are not morphologically obvious, we feel that it is more likely the result of reduced vigor caused by changes in gene expression, such as those we have observed in the liver.…”
Section: Discussioncontrasting
confidence: 54%
“…We did not see evidence that macroH2As have a crucial role in differentiation or morphogenesis during embryonic development, in contrast to some studies of in vitro ES cell differentiation and early zebrafish development (20)(21)(22). Interestingly, other studies of ES cells (42) or induced pluripotent stem cells (43) found that macroH2As are not required for in vitro differentiation and thus appear to be compatible with our results with macroH2A KO mice. While the increased perinatal death that we see in C57BL/6 double KOs could involve developmental defects that are not morphologically obvious, we feel that it is more likely the result of reduced vigor caused by changes in gene expression, such as those we have observed in the liver.…”
Section: Discussioncontrasting
confidence: 54%
“…In particular, its efficiency remains low (Mikkelsen et al, 2008;Pasque et al, 2012;Gaspar-Maia et al, 2013;Sridharan et al, 2013;Nashun et al, 2015), the extreme stability of adult somatic cell epigenetic signature makes iPSCs prone to errors (Plath and Lowry, 2011), and the use of DNA constructs and the subsequent possibility of exogenous sequence integration preclude their clinical use for safety concerns (Stadtfeld et al, 2008;Kim et al, 2009;Zhou and Freed, 2009;Seki et al, 2010). In order to circumvent these limits, smallmolecule compounds have been used to modulate the epigenetic state by inhibiting and/or activating, in a reversible way, specific signaling pathways (Huangfu et al, 2008;Ichida et al, 2009;Li et al, 2011;Hou et al, 2013).…”
Section: Erasing Of "Epigenetic Memory"mentioning
confidence: 99%
“…In addition, female ES cells depleted of both macroH2A1 and macroH2A2 are capable of undergoing Xinactivation upon differentiation (Tanasijevic and Rasmussen, 2011). Furthermore, although the details have not yet been provided, it has been reported that H2afy and H2afy2 double knockout mice are viable and fertile (Gaspar-Maia et al, 2013). We have also found that female mice deficient for both H2afy and H2afy2 are viable and fertile (unpublished observations).…”
Section: Macroh2a and Parp1mentioning
confidence: 52%